The Effect of Public Safety Policies on Crime Reduction in France - Moreau, Philippe (Journal of Public Policy and Administration, 2024)
Purpose: To aim of the study was to analyze the effect of public safety policies on crime reduction in France. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Leadership in Indian organizations plays a pivotal role in enhancing organizational learning and knowledge management by promoting knowledge sharing, continuous learning, and innovation. Effective leaders facilitate the retention of critical knowledge and improve decision-making processes, thereby driving competitive advantage and organizational success. This leadership approach fosters a culture of continuous improvement and adaptability, essential for thriving in dynamic business environments. Unique Contribution to Theory, Practice and Policy: Routine activity theory, social disorganization theory & broken windows theory may be used to anchor future studies on the effect of public safety policies on crime reduction in France. Enhance training programs for police officers to include comprehensive modules on community engagement, cultural competency, and communication skills. Encourage the adoption of diverse public safety policies tailored to the unique needs of different communities. Policymakers should prioritize flexibility and adaptability in policy design, allowing for the integration of multiple strategies based on local crime dynamics and community feedback.